Moving from broad to targeted pandemic fiscal support - Heinemann, Friedrich (EconPol policy report, 2022)
This paper conceptualizes an appropriate path for fiscal policy starting from the early phase of the pandemic up to the final transition to a post-pandemic new normal. Using this yardstick, it assesses the initial fiscal response of Member States. It exploits fiscal projections and program data to analyze the adjustment to the economic recovery. For loan guarantee and short-time work schemes, it identifies program-specific parameters that improve target precision and identifies examples of more and less convincing program designs.
Keywords: Graue Literatur